2019
DOI: 10.1111/ocr.12301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two frequencies of vibration on the maxillary canine distalization rate and RANKL and OPG secretion: A randomized controlled trial

Abstract: Structured Abstract Objectives To investigate the effects of 30 and 60 Hz vibratory stimulus on canine distalization and RANKL and OPG secretion. Setting and Sample Population Sixty patients requiring canine distalization at the Orthodontic Clinic, Prince of Songkla University. Materials and Methods Patients were randomly assigned to 30 Hz vibration (n = 20), 60 Hz vibration (n = 20), or the control group (n = 20). Modified electric toothbrushes were used to apply vibration to the randomly selected canine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…1 Several studies have reported vibration effectively accelerates the rate of tooth movement, 1,2 though conflicting results have also been reported. 3,4 Moreover, the mechanisms that surrounding cells response to vibration were still unknown. Therefore, it is of interest to examine the mechanisms that the cells respond to vibration during the mimicking of orthodontic force application in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several studies have reported vibration effectively accelerates the rate of tooth movement, 1,2 though conflicting results have also been reported. 3,4 Moreover, the mechanisms that surrounding cells response to vibration were still unknown. Therefore, it is of interest to examine the mechanisms that the cells respond to vibration during the mimicking of orthodontic force application in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies [27][28][29][30][31] and different in vivo studies [32][33][34][35][36][37] ) conducted in the past using various biomarkers and vibration devices have reported mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ahmed 35 effect of vibrating devices was analyzed on osteocalcin. Siriphan et al 36 conducted an RCT to determine the effects of vibratory stimulus on secretion of RANKL and OPG.…”
Section: Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that there is no advantage neither in the time nor in reducing pain from using vibrational devices during orthodontic treatment 55 as well as in the retraction of canines and the level of RANKL and OPG 56 .…”
Section: ) Alveolar Microperforationsmentioning
confidence: 99%